Influence of different types of contralateral suppression tones on otoacoustic emission in children with autism spectrum disorder - Jamal, Fatin Nabilah; Dzulkarnain, Ahmad Aidil Arafat; Ahmad Basri, Nadzirah; Rahmat, Sarah; Shahrudin, Fatin Amira; Che Azemin, Mohd Zulfaezal; Sidek, Shahrul Na'im; Md Yusof, Hazlina; Abd Hamid, Siti Rafiah (Korean Audiological Society and Korean Otological Society, 2025)
Background and Objectives: Auditory sensory gating deficits are abnormalities in patients with autism spectrum disorder (ASD) that may lead to sensory processing difficulties. It is particularly difficult for children with ASD to distinguish multiple auditory stimuli, which hinders them from focusing on a single auditory stimulus and separating unnecessary sounds. Suppression of otoacoustic emission (OAE) is an approach used to identify sensory gating deficits in the general population, specifically for children with ASD. This study aimed to investigate the suppression effect of various types of sound suppressors to measure their sensory gating capacity in children with ASD. Subjects and Methods: Twenty children including 10 with ASD and 10 normally developing children aged 6-12 years were recruited for this study. One accessible ear was exposed to transient-evoked OAE, whereas the other was exposed to suppressor tones. Contralateral suppressors included white noise, Quranic recitations, environmental noise, and natural sound. The magnitude of OAE suppression was determined from the difference between the OAE amplitude with and without the masker (in dB sound pressure levels) for all sound types. The sound with the highest suppression effect was determined using effect size calculation and repeated-measures analysis of variance at a 95% confidence level. A high suppression effect may suggest a high sensory gating performance, whereas low suppression may indicate low sensory gating performance. Results: Based on the analysis, the sound with the highest suppression effect was that of the waterfall. The suppression results were supported by descriptive analysis findings and effect-size calculations. Conclusions: This study provides a better understanding of the alternative sound stimuli, besides the standard white noise tone, for the assessment of sensory gating deficits among children with ASD. Sounds with a high suppression effect have the potential to be used as sound therapy interventions for children with ASD as part of rehabilitation and therapy.